Ciclo biológico daños que causa hábitos e identificación del trips de las flores frankliniella sp. del banano en condiciones de laboratorio y campo - Gallardo Guiracocha, Dennys Manuel (2006)
The present investigative work, that consisted in the study of the cycle of life, its habits and identification of the trips of the flowers on field and laboratory level, under registered of temperature and relative humidity conditions of 30.7º C and 85% respectively, it was carried out it in the farm Frutvictoria and in the laboratory of Vegetable Sanity of the Faculty of Agricultural Sciences. The objectives were: 1. to determine the biological cycle, the duration and the characteristics of the different states of development of the trips of the inflorescence of the banana at laboratory level and with field observations; 2. to recognize the habits of the insect associated with the damage in the banana fruit. 3. to identify the studied insect at genus level. At laboratory level, it was used tender fingers of banana as oviposición material and fresh flowers for feeding the immature states. The average duration in days of the different development states were: egg 2,6 ; larva I 2,0; larva II 3,3; prepupa 1,5 and pupa 2,0 days. At field level, observations of the habits of this insect associated with the damage in the fruit were made, and it was settled the instant that the adults get in the inflorescence. For the identification of this species it was carried out permanent assemblies and by using dicotomic or taxonomic keys, it was stated that the studied insect was Frankliniella parvula Hood.